The effectiveness of an exergame intervention for college students with subthreshold depression: protocol for a mixed methods study - Huang, Kexin; Li, Min; You, Simiao; Jiao, Yongliang; He, Rendong; Han, Bingyue; Pu, Yuhang; Jia, Yong; Chen, Li (Frontiers in Public Health, 2024)
Background Subthreshold depression (StD) is a condition that significantly influences the mental health and quality of life of college students and increases the risk of developing major depressive disorder (MDD). Exercise therapy has been found to be effective, but may not be enjoyable for everyone. exergames, as a form of exercise therapy, address the limitations of traditional exercise by incorporating gaming elements to make physical activity more entertaining and interactive. Currently, the Nintendo Switch is one of the most widely used exergame devices. Aims To explore the effectiveness of a Nintendo Switch-based exergame intervention on college students with StD compared to a control group, and to analyze their perceptions of the program. Methods This study will employ an explanatory sequential design, starting with a quantitative evaluation using a randomized controlled trial (RCT), followed by a supplementary qualitative study. College students identified as having StD will be randomly allocated in a 1:1 ratio into the exergame intervention group (EIG) or the control group (CG). College students in the EIG will participate in a Nintendo Switch-based exergame program for 8 weeks, with 2–3 sessions per week, lasting 50–60 min each. Participant outcomes in both conditions will be assessed at pre-intervention (T0, week 0), post-intervention (T1, week 8), 1 month after the intervention (T2, week 12), and 2 months after the intervention (T3, week 16), and a generalized linear mixed model will be used for analysis. In the qualitative part of this study, interviews will be conducted with college students with StD from the EIG at T1 to explore their experiences of receiving the intervention, and content analysis will be applied to the data collected. Discussion Nintendo provides a user-friendly platform for college students with StD to engage in electronic gaming. Limited research has explored the mental health outcomes of interventions using this type of technology in young people with StD. If the exergame program proves to be effective, it could offer a convenient and feasible intervention for further enhancing the psychological well-being of college students. Clinical trial registration This study was registered in the Chinese Clinical Trial Registry (number: ChiCTR2300068970) on 2nd March 2023.